Profil Kemampuan Berpikir Logis Matematis Mahasiswa Program Studi Pendidikan Matematika Universitas Pasir Pengaraian - Novia Sari, Riska (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2020)
This study aims to determine the profile of the mathematical, logical thinking ability of students of the Mathematics Education Study Program of the University of Pasir Pengaraian. This type of research is quantitative descriptive with the research subject, namely, students of the first semester of the Mathematics Education Study Program of the University of Pasir Pengaraian in the Introduction to Basic Mathematics (PDM) course. The research instrument used was a test description. The data analysis method used in this research is a descriptive percentage using the Microsoft Excel program. Furthermore, the analysis results are described based on data acquisition on the answers to the students’ mathematical logical thinking ability test questions presented through tables and graphs. The results showed that the mathematical logical thinking skills of class A and B students were still low. The average mathematical logical thinking ability of each class is 52.43 and 60.42. Furthermore, the most challenging indicator of mathematical logical thinking skills for grade A and B students is to draw conclusions or make estimates or predictions based on the correlation between two variables. Based on the research results, it is necessary to have an in-depth study of the causes of the low mathematical logical thinking ability of the first semester students of the Mathematics Education Study Program